Frozen Fermented Dairy Snacks with Probiotics and Blueberry Bagasse: Stability, Bioactivity, and Digestive Viability - Alejandra Hurtado-Romero; Andrea Zepeda-Hernández; Javier Cárdenas-Rangel; Ricardo Aguilar-Márquez; Luis Eduardo Garcia-Amezquita; Danay Carrillo-Nieves; Tomás García-Cayuela (Microorganisms)
The demand for healthier snack options has driven innovation in frozen dairy products. This study developed and characterized novel frozen dairy snacks fermented with probiotics (Lactobacillus acidophilus LA5; Lacticaseibacillus rhamnosus GG, and Streptococcus thermophilus BIOTEC003) and containing 2% blueberry bagasse. Four formulations (LA5, LGG, LA5-BERRY, and LGG-BERRY) were analyzed for their nutritional, physicochemical, functional, and sensory properties. High protein content (>17% d.w.) and increased dietary fiber (5.77–5.88% d.w.) were observed in bagasse-containing formulations. Stable technological characteristics were maintained, with melting rates increasing slightly during storage. Probiotic viability remained high (>8.5 log CFU/mL) after freezing and storage at −20 °C for 30 days. Post-simulated digestion, probiotics retained >7.5 log CFU/mL, while blueberry bagasse formulations exhibited significantly higher phenolic content (7.62–8.74 mg/g d.w.) and antioxidant capacity, though anthocyanin content decreased (66–68%). Sensory evaluation by 100 panelists revealed high acceptance scores (>63%), with LGG-BERRY achieving the highest score (78%). These formulations demonstrate significant potential for incorporating probiotics and functional ingredients, providing an innovative solution for probiotic delivery and the sustainable utilization of fruit by-products in the food industry.